SOSALISASI PERAWATAN DAN PERBAIKAN MESIN BABAT RUMPUT DI DESA SIBUNTUON KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN - Regi Chandela Situmorang; Epanro Natanael Simanjuntak; Gestian Janperdi Sianipar; Pastron Simanjorang; Winfonstein Naibaho; Tambos Sianturi (Abdi Jurnal Publikasi, 2025)
Community Service Lecture (KPPM) is an academic activity that aims to implement science and technology to the community through a multidisciplinary-based empowerment program. The KPPM activity carried out in Sibuntuon Village, Dolok Pardamean District, Simalungun Regency, aims to improve community welfare through various programs, such as mutual cooperation, socialization of grass cutting machine maintenance and repair, and making garbage signs. The methods used include location observation, coordination with village officials, implementation of social activities, and program evaluation. The results of the activity show that the mutual cooperation program helps increase public awareness of environmental cleanliness, while socialization of grass cutting machine maintenance provides insight for the community about the maintenance of agricultural equipment. In addition, the installation of garbage signs contributes to public education regarding the types of waste and their decomposition time. In conclusion, KPPM has a positive impact on increasing public awareness and participation in maintaining environmental cleanliness and the use of simple technology to support agricultural activities.